Analisis Karakteristik, Sikap, dan Perilaku Pengunjung Tempat Ibadah terhadap Kasus DBD - I Gde Raju Sathya Murti; Ririh Yudhastuti (Universitas Airlangga, 2023)
Background: DHF disease is an infectious disease caused by the dengue virus with a transmission pathway through the bite of the Aedes aegypti mosquito. The host factor in the epidemiological triangle, which consists of the characteristics, attitudes and behaviors of the community is estimated to be one of the supports for the occurrence of dengue cases. Buleleng Subdistrict is one of the regions in Bali Province with the highest number of dengue cases since 2016. Objectives: This study aimed to determine the relationship between the characteristics, attitudes and behaviors of the community visitors to the temple place of worship to dengue cases in Buleleng District. Methods: This study was an observational study with a cross-sectional study design model. This research was conducted in April 2022 at Jagatnatha Singaraja Temple and Taman Sari Singaraja Temple. The data in this study were obtained primaryly through questionnaires distributed to respondents, as well as secondary data related to the frequency of dengue cases sourced from the Buleleng Regency Health Office. The data obtained in this study were then processed using the Chi Square method through the spss application. Results: Characteristics possessed by the respondents related to age (p=0.914), gender (p=0.257) and knowledge (p=0.247), as well as attitudes and behaviors (p=0.841) of the temple visitors did not have a significant relationship with the dengue cases that occurred. Conclusions: The characteristics possessed by temple visitors have no connection with dengue cases that occur in Buleleng District.